The cost of sin: The effect of social norms on audit pricing - Stergios Leventis; Iftekhar Hasan; Emmanouil Dedoulis (Bank of Finland, 2013)
In this paper we provide evidence for the effects of social norms on audit pricing by studying companies belonging to the alcohol, firearms, gambling, military, nuclear power, and tobacco industries, which are often described as "sin" companies. We hypothesize that the disparities between "sin" firms operations and prevailing social norms create an adverse context which heightens the client's business risk assessment by auditors and is, thereby, reflected in the pricing decisions for audit and consulting services. Having controlled for the impact of variables relating to client attributes, auditor attributes and engagement attributes, we demonstrate that audit firms charge significantly higher audit and consulting fees to companies that deviate from prevailing social norms. Additionally, we show that audit pricing levels within the "sin" group depend both on prevailing political views and on the level of "vice" exhibited by "sin" companies.
URN:NBN:fi:bof-20140807196
Keywords: G21; G30; G34; G38; M41; 330; Social norms; audit pricing; controversial industries; sin companies